Examen Especial a la cuenta Productos Terminados de la Empresa C.A. Ecuatoriana de Cerámica, ciudad de Riobamba, período 2021. - Castillo Cuadrado, María Elizabeth (2023)
The purpose of this research project was to conduct a Special Examination of the Finished Products account of the company C.A. Ecuatoriana de Cerámica of the city of Riobamba, period 2021. The management and control of inventories within an entity are of great importance since the success of many companies depends on them. Ecuacerámica, one of the city's largest companies, has been immersed in several problems related to finished product inventory; for this reason, an evaluation of internal control over finished product inventory was evaluated to determine the degree of compliance with legal and regulatory provisions. Subsequently, the deficiencies could be evidenced with auditing techniques such as visits to the entity's facilities, observation of the processes, interviews, and personnel surveys, which significantly supported the argumentation of the different findings found. The results obtained after carrying out the examination were as follows Outdated Procedure Manuals, Inadequate Entry of Finished Product Returns, Inadequate Storage Management, Inefficient Control System for the Identification of the Finished Product, Absence of Legal Signatures in Supporting Documentation, Differences between Physical Backup Documentation and Finished Product Inventory Accounting Records.